A approach to the Colectivo de Trabajo Social Crítico Colombia (TSCC): for a critical renovation of the Social Work - Sierra-Tapiro, Juan Pablo (Prospectiva. Revista de Trabajo Social e Intervención Social, 2018)
In this article we start with an introduction placing the situation in Colombia in the possibility of building a peace process with social justice, which in turn offers an opening for a possible critical renovation of the profession, a process which we believe the Colectivo de TSCC has much to contribute in the battle of ideas, so it is important to recover their experience. For this purpose, we make a brief historical approach to its organizational process between 2004 and 2016; afterwards we propose an initial balance of its academic production, using as a base its main public documents (Manifesto of 2005, Manifesto of 2012 and Organizational principles of 2016), as well as master’s dissertations that members of the group have carried out in Brazil, putting in evidence the accumulated theoretical-political knowledge of the Colectivo de TSCC, but also exposing gaps and challenges that are necessary to work on. Finally, to conclude, some elements are exposed so that we can continue to think about the Colectivo, but beyond that, to build the possible process of critical professional renewal in Colombia.